657 Comparison of the Intramedullary Nail and Dynamic Hip Screw in the Treatment of Subtrochanteric Femoral Fractures. (4th May 2021) - Arshad, Z; Thahir, A; Rawal, J; Hull, P; Carrothers, A; Krkovic, M; Chou, D
Abstract: Introduction: A subtrochanteric femoral fracture occurs in the 5cm of bone distal to the lesser trochanter. This study aims to compare peri-operative outcomes of patients with such fractures treated with either an IMN or a dynamic hip screw (DHS). Method: We retrospectively reviewed subtrochanteric fractures presenting to our institution between October 2014 -May 2019, classifying them into two treatment groups: IMN and DHS. These groups were compared using outcomes including surgical time, blood loss, radiation dose area product (DAP), stay length, re-operation rate and mortality. Results: During the study period, 86 patients presented with a subtrochanteric fracture, 74 (86%) receiving an IMN and 12 (14%) receiving a DHS. The DHS group showed a significantly lower blood loss (776.19 ml) and DAP (150.30 mGy.cm2) compared to the IMN group (1028.74 ml and 288.86 mGy.cm2 respectively). All other outcome measures failed to reach statistical significance. Conclusions: Although National Institute for Health and Care Excellence guidelines recommend treating all subtrochanteric fractures with an IMN; the outcomes assessed did not show use of an IMN to be superior. This, along with the reduced financial cost associated with a DHS; may support the use of DHS over IMN for certain subtrochanteric fractures.